(untitled) (Research, Society and Development, 2025)
Objective: To analyze the importance of the Informed Consent Form (ICF) in dental practice, considering its legal and ethical implications, as well as its role in promoting patient autonomy and safety. Methodology: A narrative literature review with a qualitative approach was carried out through a systematic search of scientific articles in the PubMed, SciELO, Virtual Health Library (VHL), and CAPES Periodicals Portal databases. The following descriptors were used: “informed consent form,” “dentistry,” “legal responsibility,” “professional ethics,” and “patient safety,” in Portuguese, English, and Spanish. Recent and directly relevant articles were included, while studies unrelated to dental practice were excluded. Literature review: The ICF is a fundamental instrument to ensure legality and ethics in clinical dental practice. It goes beyond a formal requirement, serving as an expression of respect for the patient’s dignity and autonomy. Literature shows that the absence of the ICF, even when technical procedures are correctly performed, may lead to civil liability and compromise trust between the professional and the patient. Final considerations: It is concluded that the proper drafting and application of the ICF are essential measures to ensure the dentist’s legal protection, promote transparency in the clinical relationship, and support an ethical, responsible, and patient-centered professional practice.